Non-performing loans and profitability: evidence from listed banks in sri lanka - Mithushana, R.; Subramaniyam, A. (University of Jaffna, 2020)
Non-performing loans are the consequence of ineffective management of loan assets of the financial institutions. Tstudy's primary aim is to examine the impact of non performing loans on the profitability of listed banks in Sri Lanka. The secondary data was collected for 11 individual banks for the period from 1998 to 2018 based on Central Bank's publications. In order to test the hypothesis, time series analysis was carried out by the researcher. The study incorporates, non-performing loan as an independent variable, return on the asset as the dependent variable and capital adequacy ratio, liquidity ratio as control variables. The study employed descriptive statistics, unit root test, multicollinearity test, correlation analysis, regression analysis and co-integration test as research techniques to analyze the data. Using E-views 8 software application, the study revealed a negative significant impact of the non-performing loan on return on assets of listed banks in Sri Lanka, which implies that the increasing level of default loan repayments negatively impacts the profitability of the banks in Sri Lanka. Concerning control variables, capital adequacy ratio and liquidity ratio do not significantly impact the profitability of banks listed in Sri Lanka. The significant impact of the non-performing loan on profitability suggests that the banks should consider when they provide loans to their customers. The banks' efficient mechanisms to investigate the ability to repay the loans by the customers at the point of granting the loans. The study's findings provide more insights to the financial institutions, including banks and other finance companies, to make fruitful decisions on loan asset creation.
Keywords: Non-performing loan; Ordinary least squares; Profitability; Return on assets